A Commentary on "Dissetationes Aeneriane: Enerius' Dissertations on Various Topics - Paniagua, Freddy A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2019)
This review deals with a summary of the main topics in the book by Professor Enerio Rodriguez, the first professional to obtain the degree of "Licenciado en Psicologia" in the Dominican Republic. In that book, Professor Enerio reports his contributions in different areas of psychology, in the philosophy of science with emphasis on psychological issues, and in contemporary methodological and experimental problems in psychology.